SIRT1/P53 in retinal pigment epithelial cells in diabetic retinopathy: a gene co-expression analysis and He-Ying-Qing-Re formula treatment - Zhang, Shuyan; Wu, Jiajun; Wang, Leilei; Mu, Lin; Xu, Xiaoyu; Li, Jiahui; Tang, Guoyi; Chen, Guang; Zhang, Cheng; Zhang, Yinjian; Feng, Yibin (Frontiers in Molecular Biosciences, 2024)
Objective: Diabetic retinopathy (DR) is a severe diabetic complication, which leads to visual impairment or blindness severely. He-Ying-Qing-Re Formula (HF), a traditional Chinese medicinal concoction, has been identified as an efficient therapy for DR with retinal vascular dysfunction for decades and experimentally reported to ameliorate retinal condition in diabetic mice. This study endeavors to explore the therapeutic potential of HF with key ingredients in DR and its underlying novel mechanisms.Methods: Co-expression gene modules and hub genes were calculated by WGCNA (Weighted Gene Co-Expression Network Analysis) based on transcriptome sequencing data from high-glucose-treated Adult Retinal Pigment Epithelial cell line-19 (ARPE-19); Chromatographic fingerprint of HF was established by ultra-performance liquid chromatography coupled with high-resolution mass spectrometry (UPLC-Q-TOF-MS); The herbal compound-molecular affinity was measured by molecular docking. Reactive oxygen species (ROS) was measured by DCFDA/H2DCFDA Assay; Apoptosis was detected by TUNEL Assay Kit; while the ELISA, Western Blot, and Real-Time Quantitative Reverse Transcription PCR (qRT-PCR) were used for detecting the cytokine, protein, and mRNA expression respectively.Results: Key compounds in HF were identified as Luteolin, Paeoniflorin, and Nobiletin. For WGCNA analysis, ME-salmon ("Protein deacetylation") was negatively correlated with ME-purple ("Oxidative impairment") in high glucose-treated ARPE-19. Luteolin has high affinity with SIRT1 and P53 as indicated by Molecular docking. Luteolin has hypoglycemic effect on Type I diabetic mice. Moreover, HF and Luteolin suppress oxidative stress production (ROS and MDA), inflammatory factor expression (IL-6, TNF-α, IL1-β and MCP-1) and apoptosis as shown in the in-vivo and in-vitro experiments. Concurrently, treatment with HF and Luteolin led to an upregulation of SIRT1 and a corresponding downregulation of P53.Employing HF and its active compound Luteolin as therapeutic agents offers a promising approach to diabetic retinopathy treatment. It primarily suppressed protein acetylation and oxidative stress via the SIRT1/P53 pathway in retinal pigment epithelial cells.